Identifying factors affecting diabetes education program participation within a metro Detroit integrated health system - Denise White Perkins (Elsevier, 2021)
Diabetes self-management education and support (DSMES) can help people achieve optimal disease control, yet these services often remain underutilized. People referred to these programs by their provider can become disengaged in the program at several key steps. This study applies Classification and Regression Tree analysis to 3796 people with diabetes at a single health system based in the Detroit metropolitan area who were referred for DSMES provided by the health system to determine demographic patterns of those who were successfully contacted to schedule program intake appointments, those who did not attend their intake appointment, and those who began but did not complete their personalized DSMES program. White people > 43 years of age, those with a prior A1C value > 8.9 and those with Medicaid insurance had the highest rate of not being successfully contacted for their intake appointment. Those who did not attend their intake appointment tended to have Medicaid insurance, be younger than 48 years, and have A1C > 8.1. Within the Medicare or private insurance groups, those who did not attend were more likely to be female, of Black race and not partnered. Older males with a lower A1C (≤8.3%) had the lowest rate (34.0%) of failing to complete their DSMES plan. The data showed that almost half of those referred were not successfully contacted. The overall low completion rate of 13.2% confirms the need to examine factors predictive of participation and completion. This study highlights process improvement changes to improve personalization of outreach and engagement.